2015
DOI: 10.1016/j.cpet.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy Planning

Abstract: Incorporation of PET/computed tomography (CT) in radiotherapy planning plays a critical role in assisting gross tumor volume delineation for radiotherapy planning and delivery. As radiotherapy techniques evolve to become more conformal with the increasing use of intensity-modulated radiotherapy and stereotactic body radiotherapy, whereby sharp dose gradients exist between the target and adjacent normal tissue, accurate contouring of tumor targets is vital for the success of radiotherapy to achieve cure and loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…As EBRT techniques are constantly evolving and become more conformal with the increasing use of IMRT, whereby sharp dose gradients exist between the target and adjacent normal tissue, accurate contouring of tumor targets is very important in order to achieve cure and LR control; 18 F-FDG- positron emission tomography (PET) can provide more accurate target identification (46). It is well-known that many malignancies have higher metabolism and consequently an increased uptake of FDG than surrounding normal tissues.…”
Section: Clinical Target Volumesmentioning
confidence: 99%
See 1 more Smart Citation
“…As EBRT techniques are constantly evolving and become more conformal with the increasing use of IMRT, whereby sharp dose gradients exist between the target and adjacent normal tissue, accurate contouring of tumor targets is very important in order to achieve cure and LR control; 18 F-FDG- positron emission tomography (PET) can provide more accurate target identification (46). It is well-known that many malignancies have higher metabolism and consequently an increased uptake of FDG than surrounding normal tissues.…”
Section: Clinical Target Volumesmentioning
confidence: 99%
“…In a study published in 2008, Azrif et al (45) followed 49 patients treated for DTC and found that the majority of recurrences in TC are LR in the lateral neck and thyroid bed. Based on the data reported in the literature, guidelines, and our institutional practice, we recommend the following policy: As EBRT techniques are constantly evolving and become more conformal with the increasing use of IMRT, whereby sharp dose gradients exist between the target and adjacent normal tissue, accurate contouring of tumor targets is very important in order to achieve cure and LR control; 18 F-FDGpositron emission tomography (PET) can provide more accurate target identification (46). It is well-known that many malignancies have higher metabolism and consequently an increased uptake of FDG than surrounding normal tissues.…”
Section: Differentiated Thyroid Carcinomamentioning
confidence: 99%
“…Furthermore, numerous auto and semi-autosegmentation tools have been developed to quantify tumor activity and therefore facilitate the delineation of lung cancer reducing the interobserver variation in the definition of the GTV [7]. However, to date, there is still no consensus on which auto-segmentation tool to use for the delineation of lung tumors [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of multimodal imaging, the relevance of deformable registration is limited as these methods will most likely stay in the domain of pure algorithmic applications from a current perspective. Still it is emerging as a powerful tool in image-guided and adaptive radiotherapy for compensation of organ motion and handling of anatomical changes in the course of treatment [101][102][103][104][105][106][107][108].…”
Section: Deformable Registrationmentioning
confidence: 99%